A devil and her love song. Volume 9 - Tōmori, Miyoshi (Viz Media, 2013)
"Meet Maria Kawai--she's gorgeous and whip-smart, a girl who seems to have it all. But when she unleashes her sharp tongue, it's no wonder some consider her to be the very devil! Maria's difficult ways even get her kicked out of an elite school, but this particular fall may actually turn out to be her saving grace...Unable to tell Maria his feelings for her, Shin decides to channel all his energy into playing the piano. His hard work pays off when he lands a role in a big concert, but will Maria even be there on the day of the show?"--P. [4] of cover.